The immediate impact of the Brexit referendum on Nordic stock markets - Hartikainen, Aleksi (My University, 2018)
This thesis investigates immediate impact of the Brexit referendum on Nordic stock market returns. The aim of this paper is to find how similar the stock market reaction in Nordic countries was that of the UK. The Brexit referendum held on June 23, 2016 was about British voting whether the UK would stay or leave the European Union. The decision was unexpectedly leave. The previous literature has shown a relationship between the outcomes of uncertain political events and stock markets. This is also the case for the Brexit referendum. This paper conducts event-study to measure the effects of the referendum result on market returns. The event-study is conducted by using constant mean-return model for estimating abnormal returns and cumulative abnormal returns from logarithmic returns. Abnormal returns for event day and cumulative abnormal returns for 3, 6 and 11 days and swiftness of a market rebound are examined. The data includes stock returns for Nordic indices, two UK indices and other European indices (DAX 30, CAC 40, STOXX Europe 600) and two non-European indices (S&P 500 and Nikkei 225). The results of the event-study show that the immediate reaction on the next trading day on Nordic markets is very similar to that of the UK’s and other European markets. All Nordic, UK, German, France market indices and STOXX Europe 600 experienced significant negative abnormal returns between -3.30% and -8.85% in local currencies on the following trading day after the referendum. Despite this similar immediate reaction, the negative ARs did not last as long on Nordic markets as they did in non-Nordic Europe and Nordic markets rebound much quicker from their initial decline after the referendum. Still, overall the results highlight that the interconnectedness of European stock markets is high.
Keywords: Brexit referendum; Nordic stock market; event study; Political event; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|